2005
DOI: 10.1007/11499053_1
|View full text |Cite
|
Sign up to set email alerts
|

Lean Software Management Case Study: Timberline Inc.

Abstract: Abstract. This paper is believed to be the first documented account of a full adoption of lean by a software company. Lean techniques were devised by Toyota and other manufacturers over the last 50 years. The techniques are termed lean because they require less resource to produce more product and exceptional quality. Lean ideas have also been successful in service industries and product development. Applying lean to software has been advocated for over 10 years. Timberline, Inc started their lean initiative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…With software, each unit of work is different as are the abilities of each software engineer; therefore, unit development times can vary widely. It would, therefore, be difficult to schedule software production using Takt time [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With software, each unit of work is different as are the abilities of each software engineer; therefore, unit development times can vary widely. It would, therefore, be difficult to schedule software production using Takt time [36].…”
Section: Discussionmentioning
confidence: 99%
“…Timberline Software in Oregon in 2002 with 450 staff was the first recorded full industrial implementation of lean software development. They reported considerable improvement, but their focus on setting a common tempo or ''Takt" time for software development based on creating similar-sized work units was not easy to implement [36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another case study by Middleton et al (2005) studied a company practicing lean in their daily work for 2 years. They found that the company had many steps in the process not being value-adding activities.…”
Section: Related Workmentioning
confidence: 99%
“…When implemented in software development lean led to similar effects (cf. Morgan, 1998;Middleton et al, 2005). Even though lean principles are very promising for software development, the introduction of lean development is very hard to achieve as it requires a large shift in thinking about software processes.…”
Section: Introductionmentioning
confidence: 98%
“…For clarification, Table 4 shows a compilation of practices which have been categorised as having only lean origins [5]. Table 4 Lean (only) Software Development Practices  Jidoka (build quality in) [6]  Poka-Yoke (Defect detection and prevention) [9]  Kano analysis to link voice of the customer to requirements [40], [41]  Quality Function Deployment [41]  Value Stream Mapping [8], [6], [27], [42]  Transparency [8]  Make project status highly visible  Visualise all work items  Limit WIP (Work in Process), [43], [31]  Workload levelling "Heijunka" [6], [40]  Addressing bottlenecks [6], [44,45], [40], [27]  Deferring decision making [38], [27]  Moving variability downstream [27]  Reducing slack [22]  Measure and manage [46]  Employ Queuing Theory [25], [44,45] but measure the right things [11]  Employing Pull systems  Kanban, Limitied WIP, CONWIP (Sugimori et al, 1977;Bradley, 2007; Kniberg and Skarin, 2010), [31]  Batch control processing [47], [11]  Value stream Kaikaku [8]  Relentless reflection "Hansei" and continuous improvement "Kaizen" [6], [28],…”
Section: Agile and Lean Practicesmentioning
confidence: 99%